The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3732/ajb.92.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Only seed size matters for germination in different populations of the dimorphic Tragopogon pratensis subsp. pratensis (Asteraceae)

Abstract: Many studies have focused on the ecology of seed dimorphism, the production of two seed types by a single plant. Morphology and seed size are usually correlated, but how morphology affects germination percentage and seedling growth is poorly understood. Here we explicitly separate these effects for nine populations of the dimorphic species Tragopogon pratensis subsp. pratensis. Larger seeds yielded higher germination percentages, yet seed morphology had no additional direct effect on germination. Neither seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 41 publications
7
38
3
3
Order By: Relevance
“…3). These results agree with those of Sinefu [32]; Mabhaudhi and Modi [33]; van Molken et al [31]. Cream seeds in this study are larger and heavier than light brown and brown seeds.…”
Section: Effect Of Seed Coat Colour On Germinationsupporting
confidence: 83%
See 3 more Smart Citations
“…3). These results agree with those of Sinefu [32]; Mabhaudhi and Modi [33]; van Molken et al [31]. Cream seeds in this study are larger and heavier than light brown and brown seeds.…”
Section: Effect Of Seed Coat Colour On Germinationsupporting
confidence: 83%
“…2). These results were not in line with those of van Molken et al [31] who reported that darker seeds were heavier than lighter seeds. These results are in disagreement maybe due to the different species used in these studies.…”
Section: Thousand Grain Masscontrasting
confidence: 56%
See 2 more Smart Citations
“…Van Mölken et al (2005), also found no relationship between seed color and germination in their work with Tragopagon pratensis, but they agree that color can be an adaptation to escape predation.…”
Section: Resultsmentioning
confidence: 99%